¿Gestión de la distancia o reajuste de jurisdicciones? La propuesta de fundación de un tribunal del Santo Oficio en las Filipinas por el jesuita Francisco Velho (1658) - Rodrigues Lourenço, Miguel (2019)
This article aims to analyze the role of the Jesuit brother Francisco Velho as procurador general of the Jesuit Province of the Philippines in Madrid. During his stay at the Court, Velho presented three memorials that attempted to solve the difficult question of the spiritual dependence of the islands of Maluku. He proposed to the Consejo de Indias and the Consejo de la Suprema Inquisición the creation of a tribunal of the Holy Office in Manila. In this study we will analyze how the Holy Office was perceived in the strategy of the procurador general of the province of the Philippines. Likewise, we will consider why the project failed.